SIKAP PETANI PALA PADA KEGIATAN PEMELIHARAAN TANAMAN PALA DI DESA KAUDITAN II KECAMATAN KAUDITAN KABUPATEN MINAHASA UTARA - Nurlina ., Umawaitina; Theodora Maulina Katiandagho; Lyndon Reinhard Jacob Pangemanan (Sam Ratulangi University, 2019)
This study aims to examine how attitudes of nutmeg farmers in maintenance activities consist of weeding activities, fertilizing activities and activities for controlling weeds and pests and diseases; and identifying factors that influence the attitude of nutmeg farmers to maintenance activities. This research was conducted in Kauditan II Village, Kauditan Subdistrict, North Minahasa Regency, from November to December 2017. The sampling method was done purposively by limited only to nutmeg farmers, namely as many as 20 nutmeg farmers. The data used are primary data and secondary data. Primary data is data obtained from direct interviews with nutmeg farmers. Secondary data was obtained from the Kauditan II Village Office and the internet through google searching to obtain articles from various journal articles relating to the topic of research on the attitude of nutmeg farmers to nutmeg plant maintenance activities. The data obtained were analyzed using descriptive analysis and presented in table form. The results showed that (1) the cognitive and affective attitude of nutmeg farmers to weeding, fertilizing and controlling weed/weed plants and disease pests showed an attitude of knowing and liking with a percentage of 100%. However, the conative attitudes of nutmeg farmers to weeding, fertilizing and controlling weed/weed crops and disease pests showed that 78.33% means that farmers did three (3) activities of maintenance activities and as many as 21.67% of farmers did not implemented. *eprm*